A Novel Treatment for Ewing’s Sarcoma: Chimeric Antigen Receptor-T Cell Therapy - Lin, Zili; Wu, Ziyi; Luo, Wei (Frontiers in Immunology, 2021)
Ewing's sarcoma (EWS) is a malignant and aggressive tumor type that predominantly occurs in children and adolescents. Traditional treatments such as surgery, radiotherapy and chemotherapy, while successful in the early disease stages, are ineffective in patients with metastases and relapses who often have poor prognosis. Therefore, new treatments for EWS are needed to improve patients outcomes. Chimeric antigen receptor (CAR)-T cells therapy, a novel adoptive immunotherapy, has been developing over the past few decades, and is increasingly popular in researches and treatments of various cancers. CAR-T cell therapy has been approved by the Food and Drug Administration (FDA) for the treatment of leukemia and lymphoma. Recently, this therapeutic approach has been employed for solid tumors including EWS. In this review, we summarize the safety, specificity and clinical transformation of the treatment targets of EWS, and point out the directions for further research.